(3GdHQgGf aj Ydhe GdbQBfs - (3Ydj Hf EHQGgje Hf SYjO, CHh GdMSf GdMhaj,J (B430 (3g` s
(3ChdgG (B:s
(3JHOC HGdMOjK Ydi GdBjI (B:" (3abWY OGHQ Gdbhe GdPjf XdehG hGdMeO ddg QH GdYGdejf (B" (3ef ShQI (B" (3GdCfYGe (B" s
(3BNQgG (B:s
(3hJfJgi HJaSjQ GdBjI (B:" (3aOdGgeG HZQhQ adeG PGbG GdTLQI HOJ dgeG ShAGJgeG hWabG jNUaGf YdjgeG ef hQb GdLfI (B" (3ef ShQI (B:"(3GdCYQGa (B" s
(3bWYI dYdgG efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B250 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B5s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B24 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs